Religiusitas Tari Lengger Desa Gerduren Kecamatan Purwojati Banyumas - Robertus Suraji (Media Aplikom, 2010)
Dance of lengger is folk dance that thrives in the region of ex-Karesidenan Banyumas, especially in the agricultural area or in villages. This dance represents traces of the previous Hindu culture. A sect of Hinduism that is Cakta Tantrayana belived in Goddess of Durga as the vertility goddess. In worship ceremonies, the dance like lengger were used to request fertility. When the Hindu teaching reached Java there was transformation of meaning in this dance, caused by syncretism with Javanese belief. In Java, Goddess of Sri was believed goddess. Long ago in the area of Banyumas, dance of lengger became social the tool of society to be grateful to all Deities after harvest. In its growth later on dance of lengger naturally had meaning differentiation, of religious meaning to secular meaning. This dance today in some ways exploits the erotic. Village societies of Gerduren that till now still take care of this dance of lengger, feel that dance is the part of society life of Gerduren village. Till now they do certain rituals to take care of dance community. Rituals run by lengger community of Gerduren village relate their belief of existence of spirit as protector of dance of lengger. The spirit which is ordinarily referred to as the indang so called Kastinem. Attendance of Kastinem indang in an show of lengger is believe to give supernatural strength to the dancer of lengger. Trust about existence of indang Kastinem in their belief does not oppose their belief in God. In reading of the writer, believing of existence of indang Kastinem represents manifestation of alonging of God which is immanent, God which is near by and accompany them. Lengger community of Gerduren village have the conscious that they will not overcome problems of life with their own. They require strength aid from outside themseves. That strength they find in indang Kastinem which they trust also comes from God. Of above mentioned description, it can be concluded that dance of lengger of Gerduren village still has certain religious meaning.